2016
DOI: 10.1016/j.jep.2016.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Current therapeutic role and medicinal potential of Scutellaria barbata in Traditional Chinese Medicine and Western research

Abstract: Ethnopharmacological relevance: Scutellaria barbata is a common herb in Traditional ChineseMedicine (TCM) most often used to treat cancer. S. barbata has been found to exhibit efficacy both in vitro and in vivo on a variety of cancer types. Similarly encouraging results have been shown in patients with metastatic breast cancer from Phase Ia and Ib clinical trials. This study aims to elucidate the current use of S. barbata by TCM practitioners and in current Western research. Materials and Methods:Semi-structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…compound Lobelia oral liquid is composed of Lobelia, Sculellaria barbata , Oldenlandia diffusa , etc. Lobelia has the functions of clearing heat and detoxify, dispersing blood stasis and reliving pain (Tao and Balunas, 2016); Sculellaria barbata and Oldenlandia diffusa all can clear heat and detoxify, and have more applications in the treatment of tumor, inflammation, and often in the form of drug pairs (Zheng et al, 2018, Fan et al, 2010, Peng et al, 2018). Combined with the indications and the composition of prescription of compound Lobelia injection, it is suggested that the oral liquid of compound Lobelia oral may have curative effect on acute pharyngitis.…”
Section: Discussmentioning
confidence: 99%
“…compound Lobelia oral liquid is composed of Lobelia, Sculellaria barbata , Oldenlandia diffusa , etc. Lobelia has the functions of clearing heat and detoxify, dispersing blood stasis and reliving pain (Tao and Balunas, 2016); Sculellaria barbata and Oldenlandia diffusa all can clear heat and detoxify, and have more applications in the treatment of tumor, inflammation, and often in the form of drug pairs (Zheng et al, 2018, Fan et al, 2010, Peng et al, 2018). Combined with the indications and the composition of prescription of compound Lobelia injection, it is suggested that the oral liquid of compound Lobelia oral may have curative effect on acute pharyngitis.…”
Section: Discussmentioning
confidence: 99%
“…For example, Huaier ( Trametes robiniophila Murr) sensitizes breast cancer cells to radiotherapy through the regulation of cell cycle and DNA repair pathways (7). In vitro and in vivo testing of Scutellaria barbata in breast cancer has led to an ongoing clinical trial (8); and a recent population-based study suggests that adjunctive TCM therapy may lower the risk of mortality in patients with advanced breast cancer (9). …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in many animal models and small clinical trials have demonstrated the antitumour activity of S. barbata . The safety and efficacy of an aqueous extract of the aerial parts of S. barbata (Bezielle: BZL101) for breast cancer treatment have also been analysed in the Phase I clinical trial undertaken by Bionovo [ 32 34 ]. S. barbata and Hedyotis diffusa are the most commonly prescribed Chinese herbs for breast cancer and post-surgery colon cancer, as reported by Taiwanese nationwide surveys [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%